Pengaruh Metoda Pemberian Bumbu dan Jenis Ikan terhadap Mutu dan Nilai Sensorik pada Ikan Air Tawar Asap - Failisnur Failisnur (Institution for Industrial Research and Standardization of Industry - Padang, 2012)
Fish is a high quality food, especially because it contains a lot of protein, fat, vitamins and minerals that are very good and prospective for food source. However, it is highly perishable food in storage so that required treatment such process into smoked fish. Quality of smoked fish is strongly affected by raw materials, smoking material type, the preparation process, temperature and length of smoking and its packaging. So it was produced a smoked fish with a distinctive flavor and aroma. This study was conducted with the spices treatment method using ground spices and soaking in the extracts spices, and the treatment used a variety of freshwater fish those were lele (Clarias gariepinus), mujair (Oreochromis mossambicus), and nila (Oreochromis niloticus). Smoked fish products were then analyzed for total phenols, water content, protein, fat. Organoleptic test of taste, texture and aroma was also done. Test results showed that the best treatment was lele fish soaked in spices of extracts solution. The chemical tests were obtained total phenol; 45.05 ppm, water content; 11.06%, protein; 66.65% and fat; 5.87% respectively. Furthermore the organoleptic test were preferred with hedonic scale 4.57; 4.50; 4.02 and 4.10 respectively for the taste, texture, color and aroma.